Design of a Web-Based Student Assignment Management Information System at SMAN 19 Garut Using the Prototyping Method - rifki abdul muiz (RISTEC : Research in Information Systems and Technology, 2025)
The The development of information technology has encouraged the education sector to optimize academic data management, including student assignment management. SMAN 19 Garut currently uses a manual system for distributing, collecting, and assessing assignments, which causes inefficiency and difficulties in managing and tracking submissions. This study aims to design a web-based student assignment management information system to assist teachers and students in collecting, grading, and monitoring assignments in real time. The research method used is the Prototype method, which involves communication, quick design, prototype building, evaluation, and implementation. The system was developed using the Laravel framework, MySQL database, and responsive web-based interfaces. The results show that the developed prototype system improves the efficiency of task collection, enhances transparency in grading, and facilitates communication between teachers and students. Testing with 25 respondents (teachers and students) yielded a user satisfaction rate of 88%, indicating that the system functions according to user needs.